Establishment and characterization of stable cell-based model expressing Gfp/ SQSTM1/p62 for autophagy modulator screening - Sirigulpanit, Wipawan; Bowornruangrit, Pathompong (Health Science, Science and Technology Reviews, 2021)
Autophagy plays a key role in a number of diseases, including cancer. This study aimed to generate a stable BHK-21 cell line containing a green fluorescent protein gene (Gfp) and sequestosome 1 gene (SQSTM1/p62) for a cell-based model to screen autophagy modulator. Stable BHK-21 (Gfp/SQSTM1/p62) cell line was established in this study then examined for effectiveness in an autophagy modulator screening assay using rapamycin and chloroquine known autophagy modulators. The SQSTM1/p62 protein turnover has been measured as autophagy activity. The results showed that SQSTM1/p62 protein is active in normal growing conditions at basal level. An induction of autophagy, however, increase the degradation of SQSTM1/p62 protein causes SQSTM1/p62 protein reduction in cells while a decrease or block of this pathway causes SQSTM1/p62 protein accumulation which increases SQSTM1/p62 protein level in cells. This study indicated that stable BHK-21 (Gfp/SQSTM1/p62) cell line is available and efficient for use in an autophagy activity analysis.